(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Organic farming is a sustainable agricultural system that promotes the use of natural inputs such as crop rotation, green manure, and biological pest control to enhance soil fertility, crop yields and protect the environment. In India, organic farming has gained momentum in recent years, driven by the increasing demand for healthy food, the need to protect soil and water resources and the socio-economic benefits associated with organic farming. This research paper explores the role of organic farming as a tool for sustainable development in India. The paper reviews the current status of organic farming in India, its benefits, challenges, and opportunities for sustainable development. The paper concludes by providing recommendations to accelerate the growth of organic farming in India.